Liver Fibrosis in Primary Sjögren’s Syndrome - Androutsakos, Theodoros; Voulgaris, Theodoros A.; Bakasis, Athanasios-Dimitrios; Koutsompina, Maria-Loukia; Chatzis, Loukas; Argyropoulou, Ourania D.; Pezoulas, Vasilis; Fotiadis, Dimitrios I.; Papatheodoridis, George; Tzioufas, Athanasios G.; Goules, Andreas V. (Frontiers in Immunology, 2022)
Background Primary Sjögren’s syndrome (pSS) is a systemic autoimmune epithelitis, potentially affecting salivary epithelium, biliary epithelium, and hepatocytes. Common immunologic mechanisms might cause clinically silent liver inflammation and combined with non-alcoholic fatty liver disease (NAFLD), liver fibrosis (LF) may occur. No studies have explored the occurrence of LF in the context of NAFLD among pSS patients. Methods Consecutive pSS patients from the rheumatology outpatient clinic of the Department of Pathophysiology, and individuals evaluated in the hepatology outpatient clinic for possible NAFLD serving as comparators, underwent transient elastography (TE) to assess (LF) and liver steatosis (LS). All participants had no overt chronic liver disease. Clinical, demographic and laboratory data were collected from all participants at the time of TE. Results Fifty-two pSS patients and 198 comparators were included in the study. The median age (range) of pSS and comparators was 62.5 (30-81) and 55 (19-86) years, respectively. Both groups had similar prevalence regarding type 2 diabetes mellitus, hyperlipidemia, and body-mass index (BMI). Patients with pSS had less frequently high LS (S2, S3) (27% vs 62%, p<0.001) and significant LF (F2-4) [2 (3.8%) vs 34 (17.2%), p=0.014] than comparators. Univariable analysis showed that advanced LF was significantly associated with older age, higher LS, greater BMI and disease status (comparators than pSS); of these, only age was identified as independent LF risk factor in the multivariable logistic regression analysis. Conclusion Liver fibrosis among pSS patients is most likely not attributed to the disease pe se.